Development of an in vitro model to study hepatitis C virus effects on hepatocellular lipotoxicity and lipid metabolism - Koletzko, Leandra; Mahli, Abdo; Hellerbrand, Claus (Pathology Research and Practice, 2018)
Hepatic steatosis is common in patients infected with hepatitis C virus (HCV). Particularly in patients infected with non-genotype 3 HCV, hepatic steatosis is closely related to factors of the metabolic syndrome such as hyperlipidemia. However, the molecular mechanisms involved in this "metabolic" steatosis in non-3 genotype HCV infections are not well understood. Here, we aimed to develop an in vitro model to study the effect of genotype 1 HCV infection on hepatic lipotoxicity and lipid metabolism. Cellular lipid accumulation was induced in Huh-7 hepatoma cells transfected with HCV genotype 1b replicon (HCV+) by incubation with increasing doses of palmitic acid (C16:0) or oleic acid (C18:1 n-9) complexed to albumin mimicking hyperlipidemic conditions. Mock transfected hepatoma cells (HCV-) were used as controls. Incubation with oleic acid concentrations as high as 0.5 mM did not induce toxic effects in HCV+ or HCV- cells. In contrast, incubation with palmitic acid caused dose-dependently cytotoxic effects which were more pronounced in HCV+ compared to HCV- cells. Further analysis with subtoxic palmitic and oleic acid concentrations revealed a higher uptake of fatty acids and intracellular triglyceride accumulation in HCV+ compared to HCV- cells. Carnitine palmitoyltransferase I (CPT1) expression, indicative of mitochondrial beta-oxidation, was markedly stimulated by lipid exposure in HCV+ but not in HCV- cells. Furthermore, heme oxygenase 1 (HMOX1) expression levels increased in FA stimulated cells, and this increase was significantly higher in HCV+ compared to HCV- cells. In contrast, expression of the key enzymes of hepatic de novo lipogenesis fatty acid synthase (FASN) and stearoyl-CoA desaturase (SCD-1) was significantly reduced upon oleate exposure in HCV- but not in HCV+ cells. In summary, our newly developed cell culture model revealed effects of HCV genotype 1b infection on metabolic susceptibility to lipid accumulation and toxicity particularly to saturated lipids. These results may indicate that HCV (genotype 1b) infected individuals with hyperlipidemia may benefit from dietary or pharmacological intervention.
EVALuna2:35809